HUBUNGAN JOB DEMAND, JOB CONTROL, DAN USIA DENGAN STRES KERJA PADA PEKERJA KONSTRUKSI - Elizabeth Zavanya Manullang; Ekawati Ekawati; Siswi Jayanti (Jurnal Kesehatan Masyarakat, 2019)
Someone with job demands and workload that exceeds his/her capabilities can experience that called job stress. Job stress was really common among construction workers because of the demands of high jobs, limited time and jobs control of low workers. The influence of work stress is complex and mutually influenced by workers demand and control. According to a survey that is obtained from 5 workers, they experience insomnia, uneasiness, and irritable. This research aimed analyze how job demand, job control, and age affect the job stress of the construction workers of the ongoing projects of Gedung Dinas Kesehatan Kota and Gedung Parkir Pandanaran Semarang. The type of research that used is quantitative, with cross-sectional study. The sample is the entire population of 54 workers in the finishing section. The research instruments were General Health Questionnaire (GHQ-12) to measure work stress and questionnaires to measure job demand and job control in workers. Statistic analysis that used is rank spearmen test.The result shows that two variables were related to job stress which are job demand (p-value= 0.001), job control (p-value= 0.038), while variable that was unrelated to job stress is age (p-value= 0.947). Based on the results of the study it was recommended that the company focus on the rule of overtime hours that the workers are facing.